The association of natural resources and human conflict — natural gas and the peace process in Cyprus - Birgel, S (2018)
It is rare for a discussion of natural resources to solely refer to natural resources. Rather, to speak of natural resources often involves the entanglement of the matter with issues of a very political nature. This doctoral thesis revolves around a contemporary example of the above phenomenon with reference to the context of Cyprus and the global natural gas industry. Here, the question of “can natural gas be catalyst for peace?” has firmly taken root, largely as a result of a popularised association between a process to develop natural gas, and the seemingly intractable political peace process on the island. Indeed, the relationship espoused has been of serious commercial and political consequence. To understand exactly how, why, and exactly what has been at issue, I critically investigate the nature of the relationship established between these two expansive processes. Through over a hundred semi-structured interviews with international diplomats, industry professionals, local politicians, journalists, and academics, triangulated with detailed archival material and ethnographic work at relevant industry conferences and public forums, I explore the view of natural resources as a contingent socio-material assemblage. I expound the view of natural resources as ontologicallyrelational entities to be viewed in epistemologically processual terms. I evidence the complex ways that the axioms of time, relations of power, and the role of human emotion, have all coalesced to profoundly influence perceptions of the role, value, and nature, of natural gas. In this thesis, I find that what natural gas is understood to be and the agency it can seemingly exercise, is intimately tied to the ebb and flow of the peace process on the island in a reciprocal manner. Fundamentally, I argue that the issue of natural gas is an epiphenomenon of a Gordian knot of latent passionate political disputes commonly referred to as the ‘Cyprus Problem’. Beyond the generation of knowledge controversies regarding the future trajectory of the global natural gas industry, forecasts of supply and demand, and various development pathways, it is in relation to this complex political situation on the island from which natural gas has initially acquired meaning, significance, and power. Ultimately, the saga evidenced in this doctoral thesis is of interest to those curious of: the perennial debate vis-àvis natural resources and human conflict, the use of quantitative and qualitative research methodologies in this intellectual space, the potential political and commercial consequences of the extractive industries, and finally to those who seek a more critical appraisal of the Cyprus peace process.